2018
DOI: 10.1177/1098214018767049
|View full text |Cite
|
Sign up to set email alerts
|

So What Do You Do? Exploring Evaluator Descriptions of Their Work

Abstract: To progress as a field, evaluators must be able to describe their work to nonevaluators, and to persuade an audience they have something unique and valuable to offer. Yet anecdotal reports suggest many evaluators have difficulty describing their work. Through 42 interviews with practicing evaluators, we aimed to better understand evaluators’ experiences discussing their work, examining how evaluators describe their work to nonevaluators and the perceived challenges they face doing so. Findings suggest there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 33 publications
(35 reference statements)
2
37
0
1
Order By: Relevance
“…Overall, this study provides some insight into the varied ways in which evaluators and researchers define evaluation. Similar to the study by Mason and Hunt (2018), this study demonstrates that most evaluators, as defined in this study by self-identifing primarily as an evaluator, define evaluation in terms of the purpose of the evaluation (i.e., for rendering a value judgment or for learning, program improvement, or decision-making) and some also describe the process of evaluation (i.e., in terms of the methodology, whether outcomes or processes are examined, or participation of stakeholders). However, there were differences between evaluators and researchers in whether processes or purposes were mentioned or prioritized and what type of processes and purposes were described.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Overall, this study provides some insight into the varied ways in which evaluators and researchers define evaluation. Similar to the study by Mason and Hunt (2018), this study demonstrates that most evaluators, as defined in this study by self-identifing primarily as an evaluator, define evaluation in terms of the purpose of the evaluation (i.e., for rendering a value judgment or for learning, program improvement, or decision-making) and some also describe the process of evaluation (i.e., in terms of the methodology, whether outcomes or processes are examined, or participation of stakeholders). However, there were differences between evaluators and researchers in whether processes or purposes were mentioned or prioritized and what type of processes and purposes were described.…”
Section: Discussionsupporting
confidence: 76%
“…Other research on free associations with the word "evaluation" found that students most associated evaluation with an appraisal whereas stakeholders were more likely to associate evaluation with improvement (Schultes, Kollmayer, Mejeh, & Spiel, 2018). Furthermore, Mason and Hunt (2018) There may be more dire consequences for a lack of a single definition of evaluation. With so many definitions of evaluation existing, one could go so far as to say that anything is evaluation.…”
Section: What Is Evaluation?mentioning
confidence: 99%
See 2 more Smart Citations
“…with the word "evaluation" found that students most associated evaluation with an appraisal whereas stakeholders were more likely to associate evaluation with improvement (Schultes, Kollmayer, Mejeh, & Spiel, 2018). Furthermore, Mason and Hunt (2018) examined how evaluators describe evaluation to others and found that most evaluators tended to emphasize evaluation's purpose rather than its process, but would also vary their definitions depending on contextual factors such as a person's education, prior knowledge of evaluation, and their role in the organization. This research suggests a lack of a formal definition may make it difficult to communicate with our stakeholders or young and emerging evaluators (YEEs) what is evaluation.…”
mentioning
confidence: 99%